Ideas across borders : translating visions of authority and civil society in Europe c.1600-1840 - Mahlberg, Gaby; Munck, Thomas (London : Routledge, Taylor & Francis Group, 2024)
Building on the historical study of cultural translation, this volume brings together a range of case studies and fresh approaches to early modern intellectual history by scholars from across Europe reflecting on ideological and political change from c. 1600 to 1840. Translations played a crucial role in the transmission of political ideas across linguistic and cultural borders in early modern Europe. Yet intellectual historians have been slow to adopt the study of translations as an analytical tool for the understanding of such cultural transfers. Recently, a number of different approaches to transnational intellectual history have emerged, allowing historians of early modern Europe to draw on work not just in translation studies, literary studies, conceptual history, the history of political thought and the history of scholarship, but also in the history of print and its significance for cultural transfer. Thorough qualitative and quantitative analysis of texts in translation can place them more accurately in time and space. This book provides a better understanding of the extent to which ideas crossed linguistic and cultural divides, and how they were re-shaped in the process. Written in an accessible style, this volume is aimed at scholars in cognate disciplines as well as at postgraduate students.
Keywords: Culture diffusion; HISTORY / Europe / General; HISTORY / Modern / 17th Century; HISTORY / Modern / 18th Century